2005
DOI: 10.1111/j.1528-1167.2005.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and Cell‐mediated Autoimmunity to NMDA‐type GluRɛ2 in Patients with Rasmussen's Encephalitis and Chronic Progressive Epilepsia Partialis Continua

Abstract: Summary:Purpose: To evaluate antibody-mediated and cytotoxic T cell-mediated pathogenicity that has been implicated as the autoimmune pathophysiological mechanism in Rasmussen's encephalitis.Methods: We examined autoantibodies against the N-methyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…27,49 NMDAr encephalitis is an especially important diagnosis to consider in young patients with limbic encephalitis because the California Encephalitis Project found that the number of young patients in the study with NMDAr encephalitis was greater than those with any single viral etiology. 54 Anti-NMDAr antibodies have even been found in patients with herpes simplex virus encephalitis 55 and Rasmussen encephalitis, 56 which can further complicate the diagnostic work-up.…”
Section: N-methyl D-aspartate Receptormentioning
confidence: 99%
“…27,49 NMDAr encephalitis is an especially important diagnosis to consider in young patients with limbic encephalitis because the California Encephalitis Project found that the number of young patients in the study with NMDAr encephalitis was greater than those with any single viral etiology. 54 Anti-NMDAr antibodies have even been found in patients with herpes simplex virus encephalitis 55 and Rasmussen encephalitis, 56 which can further complicate the diagnostic work-up.…”
Section: N-methyl D-aspartate Receptormentioning
confidence: 99%
“…Lymphocytic infiltration containing predominantly T cells and sparsely B cells can be observed in surgically resected tissues from patients with Rasmussen's encephalitis (Farrell et al 1995), and local CNS immune responses in Rasmussen's encephalitis include clonal expansion of T cells responding to discrete antigen epitopes (Li et al 1997). Peripheral blood lymphocytes from patients are sensitized to GluR12 (Takahashi et al 2005). Heterogeneous autoantibodies against neuronal molecules (including GluR3, GluR12, neuronal acetylcholine receptor alpha7, and munc-18) (Yang et al 2000, Watson et al 2001, Takahashi et al 2003) and glial cells (Roubertie et al 2005) are detected in Rasmussen syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies against GluR12 have epitopes predominantly in intracellular domains, and show epitope spreading evolutionally (Takahashi et al 2003). We postulated that the autoimmune-mediated mechanism for the development of Rasmussen syndrome involves primarily cellular autoimmunity mediated by cytotoxic T cells, and evolutionarily involves humoral autoimmunity mediated by autoantibodies (Takahashi et al 2003(Takahashi et al , 2005. These autoimmune mechanisms of epileptogenesis after infections can be classified as parainfectious mechanisms ( Figure 3) (Takahashi 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the disease has been hypothesized to be associated with an autoimmune process mediated through antibodies against the glutamate receptor subunit 3, (Mastrangelo et al 2010). Takahashi et al reported that antibodies against NMDA type GluRε2 were detected in Rasmussen's encephalitis patients with and without EPC (Pleasure 2008;Takahashi et al 2003;Takahashi et al 2005). This suggests that autoantibodies against GluRε2 are important for the diagnosis of both subtypes of Rasmussen's encephalitis, independent of EPC.…”
Section: Rasmussen's Encephalitismentioning
confidence: 99%